Juridicial Review of the Appointment of An Ex-Convict of Corruption to Be A Commissioner of Bumn and Subsidiary Company of Bumn and Its Implication for Good Corporate Governance (Gcg - Kinanti Rizkika (Eduvest - Journal of Universal Studies, 2024)
This research aims to analize the appointment of an ex-convict of corruption to be a Commissioner of BUMN and the subsidiary company of BUMN from a legal perspective and its implication for Good Corporate Governance Practices. The result showed that the appointment of an ex-convict of corruption to be a Commissioner of BUMN and the subsidiary company of BUMN is considered as a violation of law because it doesn’t fulfill the Integrity aspect. The violation of integrity showed that Good Corporate Governance is not fully materialized in a corporate practice, especially BUMN and the subsidiary company of BUMN.